2012
DOI: 10.1186/1756-6614-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Safe thyroidectomy with intraoperative methylene blue spraying

Abstract: BackgroundWe aimed to minimalize operative complications by spraying of methylene blue stain on thyroid glands and the perithyroidal area.Material and methodsThe intra-operative methylene blue spraying technique was used prospectively on a total of 56 patients who had undergone primary (not recurrent) thyroid surgery for a variety of thyroid diseases. Bilateral total thyroidectomy was performed in all cases. After superior but before inferior pole ligation, 0.5ml of methylene blue was sprayed over the thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Currently, the common dyes used in China include methylene blue and patent blue. Sari et al [ 9 ] found that the parathyroid glands fade within 3 min, which is more rapid than that for thyroid tissues and lymph nodes after spraying methylene blue solution in the region around the thyroid gland. Related Chinese studies [ 10 ] have reported that methylene can be used for positioning of sentinel lymph nodes in thyroid glands, but it can stain both the parathyroid glands and lymph nodes, thus causing confusion between them and leading to mistakenly cutting parathyroid glands.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the common dyes used in China include methylene blue and patent blue. Sari et al [ 9 ] found that the parathyroid glands fade within 3 min, which is more rapid than that for thyroid tissues and lymph nodes after spraying methylene blue solution in the region around the thyroid gland. Related Chinese studies [ 10 ] have reported that methylene can be used for positioning of sentinel lymph nodes in thyroid glands, but it can stain both the parathyroid glands and lymph nodes, thus causing confusion between them and leading to mistakenly cutting parathyroid glands.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Sari et al ,. MB was used to identify the RLN by applying 0.5 mL of MB (15 mL ampoule) directly without dilution over the thyroid lobe and perilobar area, including the perithyroidal muscles, tendinous and lipoid structures giving massive blue staining of all the area with sparing of the RLN and the arteries which appeared relatively white.…”
Section: Discussionmentioning
confidence: 99%
“…Sari (Sari et al 2012) studied 56 patients who underwent thyroidectomy in which methylene blue spray was used to locate the parathyroid gland. They found that the parathyroid gland was able to absorb the blue staining and regain its original yellow color in three minutes, while other tissues took longer.…”
Section: Discussionmentioning
confidence: 99%